Digital interlooping: 3D printing of weft-knitted textile-based tubular structures using selective laser sintering of nylon powder. Issue 2 (4th May 2019) - Beecroft, Mark
ABSTRACT: This paper discusses the materialisation of 3D printed textile-based tubular forms that make use of knit's primary structures. The 3D printed forms explore both single-face and double-face weft knit structures at various sizes. 3D printing is a form of digital additive manufacturing whereby the building up of layers of material creates objects. The selective laser sintering process (SLS) uses a laser beam to sinter powdered material to create objects. This paper builds upon previous research into 3D printed textile-based structures exploring the use of SLS of Nylon powder to create flexible weft knitted structures. The results show the potential to print flexible, tubular textile-based structures at various scales that exhibit the properties of traditional knitted textile structures along with the mechanical properties of the material used to print with. The conclusion highlights the potential future development and application of such pieces within apparel-related industries.